The Effect of Project-based Learning Model on Science Learning Outcomes Reviewed from the Scientific Attitude - Suryanata, I Putu Agus; Kertih, I Wayan; Lasmawan , I Wayan (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2025)
Science is a combination of systematically arranged knowledge that discusses all matters of natural phenomena based on experiments, thoughts and observations carried out by a group of people. This study aims to determine the effect of the Project Based Learning model on the results of learning science in terms of scientific attitudes in grade V elementary school students in Cluster I, Gianyar District. The type of research conducted in this study is a quasi-experimental study with a posttest only control group design. The population of this study were all grade V in Cluster I, Gianyar District, students consisting of 281 students. A total of 83 students were selected as samples determined by random sampling techniques. The experimental class consisted of 43 people and the control class consisted of 40 people. Data collection used the multiple-choice objective test method to measure students’ science learning outcomes and non-test methods in the form of instrument questionnaires to measure the level of scientific attitudes possessed by each student. Data were analyzed using ANOVA AB analysis. The results of the study showed the F coefficient between models (FA) is 107,964 with a significance level of 0.000 and the F coefficient of interaction between models and scientific attitudes (FAB) is 5,318 with a significance level of 0.026. So it can be concluded that the project based learning model has an influence on the outcomes of science learning as seen in from the scientific attitude of grade v elementary school students in Cluster I, Gianyar District.